Morphological and reproductive differences among three charophyte species in response to variation in water depth - H Wang (Inter-Research, 2015)
Some charophyte species reproduce sexually by oospores and vegetatively by bulbils, and the proportion of branch whorls that contain reproductive organs can be used as quantitative measures of the degree of sexual reproduction. We examined inter-specific differences in the proportion of bulbils (PB) by total weight and the proportion of branch whorls containing gametangia (PG) or oospores (PO), as well as morphological and physiological differences among 3 charophyte species (Chara vulgaris Linnaeus, Chara braunii Gmelin, and Nitella gracilens Morioka) responding to variation in water depth (0.5, 1, 1.5, 2, and 3 m) in an outdoor experiment. A 2-way ANOVA contrasting species and water depth revealed that shoot elongation and the chlorophyll a to carotenoid (chl a/caro) ratio were primarily affected by water depth. However, variation among species contributed more than water depth to the differences in weight, sexual reproduction (PG and PO), and the chl a/chl b ratio. Additionally, variation among species contributed almost equally to the differences in PB that occurred among different water depths. Both Chara species extended their shoots and increased their PB in response to increasing water depth (from 0.5 to 1.5 m). However, deeper water (2 and 3 m) led to elongated shoots as well as decreased PB, PG, and PO. For N. gracilens, elongated shoots with increased water depth (from 0.5 to 3 m) occurred at the expense of both vegetative (decreased PB) and sexual reproduction (reduced PG and PO).